2017
DOI: 10.1007/s11060-017-2579-5
|View full text |Cite
|
Sign up to set email alerts
|

Walking ability in patients with glioblastoma: prognostic value of the Berg Balance Scale and the 10 meter walk test

Abstract: Primary brain tumors frequently cause considerable functional impairments and the survival time when diagnosed with glioblastoma is 14.6 months. The aim of this study was to examine if baseline postural control and walking ability in patients with glioblastoma could predict long term walking ability and 1 year mortality. Data were gathered from prospective recordings in a brain cancer database supplemented by retrospective review of electronic patient records. We included 109 patients with glioblastoma, 47 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The study used BI, FIM, and additionally BBS to assess physical functioning, as these scales had previously been applied with positive recommendations in BT patients [14,16,19,21,34] to assess problems reported by the participants or observed by the physiatrist, and which were linked to the ICF categories [36,37]. The FIM scale is a daily living activity scoring system that may objectively determine impairments in different domains [15,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study used BI, FIM, and additionally BBS to assess physical functioning, as these scales had previously been applied with positive recommendations in BT patients [14,16,19,21,34] to assess problems reported by the participants or observed by the physiatrist, and which were linked to the ICF categories [36,37]. The FIM scale is a daily living activity scoring system that may objectively determine impairments in different domains [15,37].…”
Section: Discussionmentioning
confidence: 99%
“…The Berg Balance Scale (BBS) is a widely used clinical test assessing balance abilities in adults, used also among BT patients [19,20]. BBS aims to objectively determine patients' ability (or inability) to safely balance during a series of tasks and can predict walking suitable for patients after rehabilitation therapy [19][20][21]. The qualitative tool assesses balance by means of functional tasks such as reaching, bending, standing, and transferring which involves most components of postural control [20].…”
Section: Berg Balance Scalementioning
confidence: 99%
See 1 more Smart Citation
“…For characterization of the sample, the following instruments were applied: the Orpington Scale to classify the severity and estimate the prognosis of functional improvement [30,31], the Fugl Meyer Evaluation Scale (FMS) to assess motor and sensory impairment [32], and the Berg Balance Scale to evaluate balance ability [33]. In addition, hand muscle function was evaluated through palmar grip dynamometry (Saehan® brand dynamometer) [34], and unilateral manual dexterity was measured with the Box and Block Test (BBT) [35].…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…Most of the previous studies were rehabilitation programs for patients who had chronic neurological symptoms and long-term impaired body functions. [23][24][25] In the area of patients who had cranial surgery, a previous study concerning early recovery after surgery (ERAS) programs was found to have encouraged patients to have early mobility from the first 24 hours after surgery. Furthermore, patients who received the ERAS program had early recovery with reduced LOS in hospital.…”
Section: Introductionmentioning
confidence: 99%